Effect of bariatric surgery on mitochondrial remodeling in human skeletal muscle: a narrative review - Ge, Xiaochuan; Wang, Zhe; Song, Yafeng; Meng, Hua (Frontiers in Endocrinology, 2024)
In the context of obesity epidemic as a major global public health challenge, bariatric surgery stands out for its significant and long-lasting effectiveness in addressing severe obesity and its associated comorbidities. Skeletal muscle mitochondrial function, which is crucial for maintaining metabolic health, tends to deteriorate with obesity. This review summarized current evidence on the effects of bariatric surgery on skeletal muscle mitochondrial function, with a focus on mitochondrial content, mitochondrial dynamics, mitochondrial respiration and mitochondrial markers in glucolipid metabolism. In conclusion, bariatric surgery impacts skeletal muscle through pathways related to mitochondrial function and induces mitochondrial remodeling in skeletal muscle in various aspects. Future studies should focus on standardized methodologies, larger sample sizes, and better control of confounding factors to further clarify the role of mitochondrial remodeling in the therapeutic benefits of bariatric surgery.